Football coaches' perceptions of the introduction, delivery and evaluation of visual exploratory activity - Pulling, C.; Kearney, P.; Eldridge, D.; Dicks, M. (Psychology of Sport and Exercise, 2018)
The purpose of the study was to examine how visual exploratory activity (VEA) is introduced, delivered, and evaluated by football coaches. Further, this study aimed to explore whether distinct groups of football coaches existed who differed in their approach to the delivery of VEA training and, if so, whether there were differences in the demographics of the coaches across these differentiated groups. The participants in the study consisted of 303 current football coaches who completed an online survey comprised of three sections and 12 items. Cluster analysis identified three clusters of coaches, which were distinguished by the extent to which they engaged in the delivery of VEA training: Low delivery of VEA training (n = 68), Moderate delivery of VEA training (n = 153) and High delivery of VEA training (n = 82). The High delivery of VEA training cluster were likely to provide more feedback/instruction on VEA; they designed an activity or part of a session to focus on VEA more often; and the percentage of sessions they would primarily focus on VEA was higher compared to the Moderate delivery of VEA training and Low delivery of VEA training clusters. It appears that a higher coaching qualification and experience (years coached and number of hours coached per week) leads to a positive attitude of coaching VEA. Future research regarding VEA should involve direct observations of coaching behaviour in relation to VEA, as well as interviewing the coaches on the delivery of VEA training. From a practical perspective, there is a need for further research to explore practice design and how this can be developed to enhance the use of VEA by performers.